Rekayasa Elektrikal dan Konstruksi: A Preliminary Review - Masykur Kimsan (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2024)
Electrical engineering is an integral and currently crucial component across various fields. With the advancement of technology, electrical engineering has become essential in modern construction, demanding the integration of efficient and reliable electrical systems to ensure optimal operation and building sustainability. Advanced technologies such as the internet of things (iot), artificial intelligence (ai), and renewable energy present not only challenges but also significant potential for innovation in electrical engineering within construction projects. The integration of these technologies aims to enhance system efficiency and safety while playing a crucial role in environmental sustainability by reducing carbon footprints and increasing energy efficiency. Case studies from recent projects in indonesia and asia have demonstrated successful implementation and valuable lessons learned. The application of these technologies in electrical engineering shows significant potential in creating more efficient, safe, and sustainable infrastructure projects. This review is intended to provide in-depth insights for professionals in the fields of construction and electrical engineering. Furthermore, it aims to serve as a critical reference for the development of infrastructure projects that prioritize efficiency, safety, and sustainability. Through this comprehensive study, it is hoped to foster further innovation and the adoption of the latest technologies that will optimize the performance and sustainability of future infrastructure projects.